Meta-Analysis of Seroprevalence and Prevalence of Influenza A Viruses (Subtypes H3N2, H3N8, and H1N1) in Dogs - Ivan Ramos-Martínez; Edgar Ramos-Martínez; Manuel Saavedra-Montañez; Saraí Santos-Paniagua; René Segura-Velázquez; Onasis Vicente-Fermín; Mayte Martínez-Aguirre; Juan C. Ramos-Martínez; Sheila Irais Peña-Corona; Rodolfo Pastelin-Palacios; José Ivan Sánchez-Betancourt (Animals)
Influenza A is a zoonotic disease that affects dogs, pigs, horses, poultry, and birds. In this report, a meta-analysis according to PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) was conducted. Studies of influenza A viruses in dogs providing prevalence or seroprevalence in any location worldwide were included. The results in this study show that the seroprevalence for the H3N8 influenza subtype was 7.96% (95% CI: 2.03–16.8, p < 0.001), for the H3N2 subtype was 7.44% (95% CI: 4.51–10.5, p < 0.001), and for the H1N1 subtype was 3.10% (95% CI: 0.890–6.01, p < 0.001). In the case of the prevalence analysis, a prevalence of 0.395% (95% CI: 0.160–2.44) for the H3N8 subtype. For the H3N2 subtype, a prevalence of 17.8% (95% CI: 6.66–32.6, p < 0.001) was found. No publication bias was observed in the studies evaluating seroprevalence in the H3N2 and H1N1 subtypes. In the H3N8 subtype, Begg’s test indicated publication bias, but Egger’s test showed no bias. It is essential to know the approximate prevalence and seroprevalence worldwide of canine influenza, so this study reports the presence of influenza subtypes in dogs, placing this species as a reservoir for human, swine, equine, and avian influenza A viruses.